Food sovereignty and convergence spaces. (November 2019) - Claeys, Priscilla; Duncan, Jessica
Abstract: In this paper we reflect on the Civil Society and Indigenous Peoples' Mechanism to the UN Committee on World Food Security as a policy convergence space for the global food sovereignty movement. Addressing a gap in the convergence literature around inclusivity, we assess the extent to which the Mechanism is a diverse and inclusive space. More specifically, we analyze whether constituencies and quotas have worked as effective tools to protect diversity while avoiding fragmentation. We further contribute to the growing literature on convergence spaces by highlighting what changes and challenges occur when convergence is situated and managed in relation to a more formal institutional space. Analyzing how it has addressed the two challenges of fragmentation and institutionalization, we show how the Mechanism has moved towards greater inclusivity and diversity by reinforcing weaker constituencies, changing its name, and opening up to new constituencies. At the same time, we identify five issues which require further attention if the Mechanism is to remain an inclusive convergence space: risk of a concentration of power; the role of NGOs; gender equality and generational balance; multiple identities that cut across constituency categories; and, tensions related to sub-regions.